Role of Inflammatory Markers in Predicting Severity in COVID-19 Patients at Tertiary Care Hospital, Ujjain (M.P.) - Sarraf, Shivmohan; Singapurwala, Mustafa; Jain, Harshit; Singh, Ravendra; Julka, Arti (Journal of Pulmonology and Respiratory Research, 2023)
Originating from China in 2019, the novel Coronavirus Disease 2019 (COVID-19) pandemic had badly affected most of the world causing immense morbidity and mortality. The disease in moderate to severe cases was characterized by intense inflammation leading to ARDS and hypercoagulable states leading to thrombo-embolism and mortality. Aim: This study aimed to explore the association of inflammatory biomarkers with COVID-19 disease severity in our hospital which became a dedicated COVID hospital during the pandemic.